Mindfulness mediates the relation between cognitive reappraisal and test anxiety - Vizioli, Nicolás Alejandro (2025)
Objective. This study analyzed the relationship between mindfulness, cognitive reappraisal, expressive suppression, and test anxiety in university students. The first hypothesis proposed that cognitive reappraisal, expressive suppression, and mindfulness would be negatively associated with test anxiety and its dimensions. The second hypothesis stated that mindfulness would mediate the relationship between cognitive reappraisal and test anxiety. Method. 275 University students of legal age voluntarily completed standardized questionnaires in digital format. Results. Results showed that mindfulness was significantly associated with cognitive reappraisal and with several dimensions of test anxiety. Mediation analysis indicated that mindfulness partially explained the relationship between cognitive reappraisal and test anxiety. These findings provide evidence for the mediating role of mindfulness in the relationship between emotion regulation and academic anxiety and highlight the importance of considering test anxiety from a multidimensional perspective.